Performance characteristics of a fan filter unit (FFU) in mitigating particulate matter levels in a naturally ventilated classroom during haze conditions. (2nd December 2020) - Tham, Kwok Wai; Parshetti, Ganesh Kashinath; Anand, Prashant; Cheong, David Kok Wai; Sekhar, Chandra
Abstract: The performance of a low‐cost fan filter unit (FFU) in mitigating hazardous particulate matter (PM) levels in a naturally ventilated school classroom is presented. The FFU can be considered as a simplified mechanical ventilation and air‐conditioning system without heating and cooling functions. The FFU improves indoor air quality through introduction of cleaned outdoor air to flush out internally generated heat and moisture and reducing infiltration by maintaining indoor pressurization. Indoor particle number concentrations were reduced between 85% and 95%. The particle removal performance (PRFFFU ) of the FFU is determined and incorporated into the augmented façade penetration factor ( P aug ). A case‐specific recursive dynamic mass balance model is used to characterize the infiltration factor ( F INF ), deposition rate ( K ), and the penetration efficiency ( P aug ) from continuously monitored indoor and outdoor mass concentration levels. Computed " P aug " (0.07, 0.09, and 0.13) and " F INF " (0.06, 0.08, and 0.11), respectively, for PM10, PM2.5, and PM1 suggest that exposure to PM was significantly reduced indoors. The effectiveness of the FFU for reduced " F INF " and " P aug " may be attributed to its superior filtration, dilution, and exfiltration mechanisms. In comparison with alternative PM mitigation solutions, the FFU is effective, affordable, and sustainable.